PERANAN KEPALA SEKOLAH DALAM MENGEMBANGKAN LEMBAGA PENDIDIKAN DI MTSN 2 JOMBANG - Fajria Nur Khasanah; Didin Sirojudin (The Center for Research and Community Service of Islamic Institute of Hasanuddin Pare-Kediri, 2023)
ABSTRACT The principal is the leader of the school or educational unit where he gives and takes lessons. The principal not only acts as a leader, but the principal also has various roles, one of which is as an educator. This research was conducted with the aim of knowing the role of the principal in developing educational institutions at MTsN 2 Jombang. This study used qualitative research methods. Data collection techniques in this study by observation, interviews, and documentation. The results showed that the principal has tried to improve the quality of educational institutions and also the quality of human resources by holding trainings, seminars and so on. The principal is very concerned about the development of student activities in every teaching and learning activity. The principal has also tried to provide the best facilities to support the convenience of teaching and learning for students. However, every learning process does not always run smoothly, there must be inhibiting and supporting factors. One of the inhibiting factors is differences from various student backgrounds because students come from various regions and also cultural differences. And one of the supporting factors is the existence of various academic and non-academic achievements that have been achieved by students. However, every learning process does not always run smoothly, there must be inhibiting and supporting factors. One of the inhibiting factors is differences from various student backgrounds because students come from various regions and also cultural differences. And one of the supporting factors is the existence of various academic and non-academic achievements that have been achieved by students. However, every learning process does not always run smoothly, there must be inhibiting and supporting factors. One of the inhibiting factors is differences from various student backgrounds because students come from various regions and also cultural differences. And one of the supporting factors is the existence of various academic and non-academic achievements that have been achieved by students. Keywords: Principal, Development, Educational Institution ABSTRAK Kepala sekolah adalah pemimpin sekolah atau satuan pendidikan tempat memberikan dan mengambil pelajaran. Kepala sekolah bukan hanya berperan sebagai seorang pemimpin, melainkan kepala sekolah juga memiliki berbagai peran salah satunya sebagai seorang pendidik. Penelitian ini dilakukan bertujuan untuk mengeahui peran kepala sekolah dalam mengembangkan Lembaga Pendidikan di MTsN 2 Jombang. Penelitian ini menggunakan metode penelitian kualitatif. Teknik pengumpulan data dalam penelitian ini dengan observasi, wawancara, dan dokumentasi. Hasil penelitian didapatkan bahwa kepala sekolah telah berusaha untuk meningkatkan kembali kualitas lembaga pendidikan dan juga kualitas sumber daya manusianya dengan mengadakan pelatihan-pelatihan, seminar dan lain sebagainya. Kepala sekolah sangat memperhatikan perkembangan kegiatan siswa pada setiap kegiatan belajar mengajar. Kepala sekolah juga telah berusaha untuk memberikan fasilitas yang terbaik guna menunjang kenyamanan belajar mengajar para siswa. Akan tetapi setiap kepemimpinan pasti mengalami berbagai hambatan-hambatan. Salah satu faktor penghambatnya yakni perbedaan dari berbagai latar belakang siswa dikarenakan siswa yang berasal dari berbagai daerah dan juga perbedaan budayanya. Dan salah satu faktor pendukung yakni dengan adanya berbagai prestasi akademik maupun non akademik yang telah di capai oleh para peserta didik. Kata Kunci: Kepala Sekolah, Mengembangkan, Lembaga Pendidikan